Geographical distribution of a disjunct population of Herpsilochmus sellowi Whitney & Pacheco, 2000 (Aves, Thamnophilidae) and implications for the conservation of the physiognomies of quartzarenic carrascos from the middle Tocantins river, Cerrado biom - Dornas, Tulio; Haidar, Ricardo Flores; de Morais, Fernando (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2021)
Caatinga Antwren (Herpsilochmus sellowi) is widely distributed in northeastern Brazil with disjunct populations: on the Middle Tocantins river (Tocantins state) and Serra do Cachimbo (Pará state). The Middle Tocatins river disjunct population occurs in dense tree-shrub vegetation, on very sandy soil, being comparable with Amazonian campinaranas, locally called carrasco. The Area of Occupation (AOO) and Extent of Occurrence (EOO) of H. sellowi in this area did not exceed 2,500 and 5,000 ha, respectively. We present 20 new records of the species in the central region of Tocantins state, expanding the geographic distribution of this population to an AOO of 18,254 ha and EOO of 49,600 ha, decreasing the degree of threat of regional extinction of the species. We reiterate that the carrascos and sandy soil campinarinas vegetation enclaves with H. sellowi be defined as a preservation/conservation zone in the zoning of the APA Lago de Palmas sustainable use protected area. We recommend that the other identified areas in the perimeters we studied be converted into other categories of protected areas, ensuring the broadest protection of this population of H. sellowi, as well as the unique vegetation and landscape elements that demand study.
Keywords: Cerrado biome; Caatinga Antwren; Campinaranas enclaves; Carrasco vegetation; Tocantins river; Quartzarenic soils